Managing Marine Resources Sustainably – The ‘Management Response-Footprint Pyramid’ Covering Policy, Plans and Technical Measures - Cormier, Roland; Elliott, Michael; Borja, Ángel (Frontiers in Marine Science, 2022)
The plethora of human activities and their pressures and impacts in the oceans require managing at local, national, regional and international scales. This requires management responses in a programme of measures to determine (a) the area in which the human activities take place, (b) the area covered by the pressures generated by the activities on the prevailing habitats and species in which pressures are defined as the mechanisms of change, and (c) the area over which any adverse effects (and even benefits) occur on both the natural and human systems. The spatial and temporal scales of these leads to the concepts of activity-, pressures-, effects- and management responses-footprints, defined here. These footprints cover areas from tens of m2 to millions of km2, and, in the case of management responses, from a large number of local instruments to a few global instruments thereby giving rise to what is termed the management response-footprint pyramids. This may operate from either bottom-up or top-down directions, whether as the result of local societal demands for clean, healthy, productive and diverse seas or by diktat from national, supranational and global bodies such as the United Nations. These concepts are explained and illustrated using marine examples based on experience from many jurisdictions.